Linaria becerrae (Plantaginaceae), a new endemic species from the southern Spain, and remarks on what Linaria salzmannii is and is not - Blanca, Gabriel; Cueto, Miguel; Fuentes, Julián (Phytotaxa, 2017)
A new species of the genus Linaria is described, illustrated and compared with its morphologically closest relatives from L. sect. Versicolores: L. salzmannii, L. viscosa and L. spartea. Furthermore, the identity of L. salzmannii, with which it has been usually misidentified, is discussed. The new species occurs on molasse substrates, forming part of communities of ephemeral annual herbs, in the province of Málaga (southern Spain), near the locality El Chorro. Synonymy is revised for the concerned names, and an identification key is reported for the Iberian taxa of L. sect. Versicolores.